Valoração e sustentabilidade da pesca artesanal de Curuçá e Colares, Estado do Pará: uma análise das externalidades de um projeto portuário na percepção dos pescadores. - BEGOT, Ligia Henriques (Universidade Federal do Pará, 2018)
The Amazon coastal zone is a region of extreme socio-cultural, economic and ecological importance, with the possibility of installing the Porto do Espadarte project in one of the coastal states of the state of Pará, such as Curuçá or Colares. The construction of a large work affects the population, especially artisanal fishermen, due to static and dynamic externalities on the use of natural resources. In this regard, this is an early process for the installation of communities that can have a major project, such as the development of socio-economic activities and the creation of a large project such as the Port of Espadarte, an artisanal fishing activity and maintenance of fishing communities . Based on the perception of the artisanal fishermen of the municipalities of Colares and Curuçá. The methodology used was the Integrated Continuous Evaluation Method (MIAC), with the application of the methods of Disposal to Pay (DAP) and Disposition to Accept (DAA). The resources correspond to an artisanal fisherman with a socioeconomic interdependence of coastal fishing resources, with a diversity in strategies and fishing gear. Introducing swaps and the understanding of externalities that are not caused by the port, especially the negative externalities. The DAP and DAA models were constructed with socioeconomic, environmental and fishing parameters corresponding to estimates that predict the Ecological Economy, presenting the variables such as Sex, Schooling, Socioenvironmental Indicator, Fishing Time and Fishing Type. The average values of DAP and DAA show a growth rate of R$ 6.3 million and R$ 64.5 million. Conclusion of the DAP model, with greater significance, expression of total economic value of resources for the artisanal fishermen of Curuçá and Colares, as well as the fishermen who have a high perception about the natural resources and environment, possessing a clear knowledge about the externalities positive and negative that can be obtained from this great work. The main rules of this module are the environmental governance standard for artisanal fishermen, the main rules for public policies that lead local development of better living conditions for affected people, reducing the social, environmental and cultural consequences to locaties.